A descriptive-contrastive analysis of some English and Davao Visayan clause structures - Regodon, Caridad (Estabillo) 1925- (publisher not identinfied], 1965)
This study provides a descriptive-contrastive analysis of some English and Davao Visayan Clause structures. This includes comparable descriptions of the clause structures in the two languages for pedagogical purposes. The descriptive analysis is based on the tagmemic approach by Benjamin Elson and Vilma Pickett, adapted from Pike and Longacre's string continuent analysis. The procedure employed is based on the Lado approach expounded in his book, Linguistics Across Cultures.